Method for customized design of a quasi-stationary CPC-type solar collector to minimize the energy cost. (April 2019) - Osório, T.; Horta, P.; Collares-Pereira, M.
Abstract: The use of solar thermal energy to supply industrial process heat is one of the most promising areas for solar market growth. Whereas low temperature (T < 100 °C) applications and the higher end of medium temperature applications (200 °C < T < 400 °C) are well suited for stationary collectors and line-focusing tracking collectors, respectively, a gap in collector offer exists in between. Non-imaging CPC (Compound Parabolic Concentrator) type concentrators show the potential to cover this gap when designed for a quasi-stationary (or seasonally tilt adjusted) operation, making use of the advantages of concentration while not depending on tracking systems, thus presenting a great potential for low cost production. Many factors, from the geometrical design to materials, production, installation conditions, O&M, operation temperature and resource availability have an impact on the performance and cost, and must be accounted for to find the optimum collector design. In this study, we developed a method for a customized design of a quasi-stationary CPC-type collector in which the Levelized Cost of Heat delivered is minimized. This methodology, based on a database of several collector configurations, will make it easier for any manufacturer to identify the most cost-effective solution for a particular installation. Highlights: Quasi-stationary CPC-type collector concept for medium temperature applications. Full flexible mounting collector from vertical facades to horizontal grounds. Customized design methodology for the minimization of an energy cost function. Energy yield and energy cost comparison for two different exemplary installations.